EFEKTIVITAS ANTI JERAWAT SEDIAAN KRIM EKSTRAK ETANOL DAUN NANGKA (Artocarpus heterophyllus Lam.) TERHADAP Propionibacterium acnes - Hafizhatul Abadi; Vivi Eulis Diana; Jacub Tarigan; Tetty Noverita Khairani; Tri Sundari (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
Jackfruit (Artocarpus heterophyllus Lam.) leaves have medicine potential, such as an antibacterial in anti-acne treatment contain flavonoids, tannins and saponins. The study aims to determine whether the ethanol extract of jackfruit leaves 96% can be formulated and determined the effectiveness of concentration preparation in inhibiting the Propionibacterium acnes bacteria. The preparation of cream preparations used a concentration of 20%, 30% and 40% jackfruit leaf ethanol extract. Then carried out the evaluation test of the preparation including the organoleptic test, homogeneity test, spreadability test, and pH test. Furthermore, the antibacterial effectiveness test was carried out by using the diffusion method. The results of evaluation test for cream preparations which included organoleptic tests with the results of three concentrations meeting the requirements, the homogeneity test and the dispersion test of the preparations, the results meet the specified conditions and the results of the pH test with the three concentrations of preparations that met the specified pH requirements. And it can inhibit the growth of Propionibacterium acnes bacteria with an inhibition zone of 7.5 mm at a concentration of 20%, 11 mm at a concentration of 30%, and 11.7 mm at a concentration of 40%. Antibacterial effectiveness test using positive control had an inhibition zone of 25.9 mm. The conclusion of this study is that the ethanol extract of jackfruit leaves can be formulated into anti-acne cream preparations.